Thermal analysis and switching performance of a 1.7 kV SiC power MOSFET under high-frequency operation and double pulse testing - Arith, Faiz; Mohd Seth, Muhammad Najmi; Zulkifle, Nurul Amirah; Noorasid, Nur Syamimi; Omar, Ghazali; Muhammad Mustafa, Ahmad Nizamuddin (Institute Of Electrical And Electronics Engineers Inc., 2025)
This study presents a comprehensive simulation analysis of 1.7 kV SiC Power MOSFETs (SiC) compared to conventional Si power MOSFETs (Si1 and Si2) focusing on thermal behavior, switching performance, and efficiency under various operating conditions. LTspice simulations over 5000 switching cycles revealed that the SiC MOSFET exhibited lower conduction losses and superior thermal stability, with higher thermal fluctuations at 50 kHz ( 0.32664 ∘ C per cycle) due to prolonged on-times, while higher frequencies at 200 kHz reduced fluctuations to 0.13397 ∘ C per cycle. Meanwhile, under the same conditions, Si MOSFETs experience higher power dissipation and poorer thermal management. Double pulse testing at varying temperatures demonstrated the SiC MOSFET has superior efficiency, peaking as high as 99.61 %, 99.55 %, and 99.44 % at 500 V, 1000 V, and 1500 V, respectively, at 150 ∘ C. A boost converter test using a 0.5 mH inductor and 200 μ F capacitor further evaluated energy conversion performance, showing minimal voltage deviation in SiC MOSFETs, with outputs of 1359.32 V, 1360.57 V, and 1358.56 V at 25 ∘ C, 100 ∘ C, and 150 ∘ C, respectively, compared to the theoretical 1360 V, while Si MOSFETs displayed greater voltage drops and efficiency losses. These results confirm that SiC Power MOSFETs provide significantly higher efficiency, lower thermal resistance, and superior performance in high-voltage, high-power applications compared to conventional Si MOSFETs.